Fraudulent financial reporting: a basic analysis - Puat Nelson, Sherliza (2011)
For the past decade, little had been discussed on the much taboo subject among companies, as the consequences are massive either legally, financially, and morally. It is important to distinguish between error and fraud, as error is an unintentional mistake in financial statements. However, fraud is said to occur with intention in order to conceal or benefit certain parties. Many companies face occupational fraud and abuse that involve a wide variety of conduct by executives, employees, and managers, ranging from sophisticated investment swindles to petty theft. However, the common violations are usually corruption, asset misappropriation and fraudulent statements. Subsequently, fraud for or against a company can take the form of fraudulent financial reporting. The objective of the study is to examine the differences between fraud and non-fraud firms on the firm characteristics as well as director characteristics.